Analisis Faktor-Faktor yang Mempengaruhi Keaktifan Kader Posyandu di Kelurahan Kebun Bunga Wilayah Kerja Puskesmas Sukarami Palembang Tahun 2017 - Yesi Adesma (IKEMAS: Jurnal Ilmu Kesehatan Masyarakat, 2018)
Activity of posyandu cadres is a behaviour or an action which can be seen from one?s regularity or involvement of cadres in various event held by posyandu both inside or outside the organization. The attendance of cadres has significant advantage toward posyandu event without whom it is difficult to run well. This study aims at analyzing the relationship between education, knowledge, training, facility and appreciation with posyandu cadres activity. It is a cross-sectional quantitative analytical desciptive study the data of which were collected using questionnaire from 32 samples of posyandu cadres. It was conducted in Posyandu of Kebun Bunga Subdistrict of Sukarami Community Health Centres Working Area of Palembang in April ? May 2017. The results show that there were 15 active posyandu cadres among the respondents and 17 were less active. The results also show that there waere no significant correlation between training (p=0.340) with activity (p=0.896); and there were significant correlation between knowledge (p=0.040), facilities (p=0.005) and appreciation (p=0.003) with the activity. Among the variables, the most dominant factor was knowledge in relation to the activity. Based on the results, it is suggested that community health center staff add the knowledge of the cadres, complete posyandu facilities, and give appreciation in order that they become more active to provide health services.